Nematode assemblages, food web indices and metabolic footprints in maize-pigeon pea agro-ecosystems - Maina, Samuel; Karuri, Hannah; Mugweru, Julius (Elsevier Ltd, 2022)
Pigeon pea (Cajanus cajan L.) and maize (Zea mays L.) are important food crops in developing countries due to their multiple benefits. However, their production is constrained by plant-parasitic nematodes (PPN) which cause significant yield losses. Understanding the nematode-based soil food web structure in maize-pigeon pea agroecosystems will allow sustainable PPN management by improving soil health. This study explored nematode community assemblages, indices and metabolic footprints in maize-pigeon pea agroecosystems in Mbeere South, Embu County, Kenya. Soil samples were collected from Gachuriri, Irabari, Kanduu, Kangeta, Kangungi, Kaninwathiga, Karimari and Mutugu regions. The recovered nematodes were identified to the genus level. There were 41 nematode genera across the eight regions. Longidorus spp., Heterocephalobus spp., Cervidellus spp., Mesorhabditis spp. and Mononchus spp. differed significantly across the regions. Meloidogyne spp., Scutellonema spp., Rotylenchulus spp. and Pratylenchus spp. were the most prevalent genera although their abundance was not statistically different across the regions. Using the structure and enrichment indices, soil food web in Irabari was degraded, whereas the other seven regions were structured. The main energy channel of organic matter decomposition in the studied regions was dominated by fungivores. There were no differences in metabolic footprints expect for bacterivore footprint. The occurrence of Hoplolaimus spp. and Xiphinema spp. showed a negative correlation with N, C, Mg and Na. This work provides useful insights into the maize-pigeon pea nematode soil food web structure and function which can be used in improving their yields and soil health
Journal Article
Keywords: Cajanus cajan; Metabolic footprint; Nematode community assemblages; Soil health; Zea may